2021
DOI: 10.1016/j.jaad.2020.08.126
|View full text |Cite
|
Sign up to set email alerts
|

Occupational dermatoses among front-line health care workers during the COVID-19 pandemic: A cross-sectional survey

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 4 publications
1
19
0
2
Order By: Relevance
“… 34 , 36 A survey of 390 HCWs, reported that 61.7% had worsening of their skin since the start of COVID-19 pandemic with acne being the most frequently reported. 32 HCWs had more symptoms compared to non-HCWs due to the increased duration of facial PPE worn and the use of N95 respirators. 25 Another study in non-HCWs showed cloth masks led to fewer acne flares compared to surgical masks.…”
Section: Facial Ppementioning
confidence: 98%
See 3 more Smart Citations
“… 34 , 36 A survey of 390 HCWs, reported that 61.7% had worsening of their skin since the start of COVID-19 pandemic with acne being the most frequently reported. 32 HCWs had more symptoms compared to non-HCWs due to the increased duration of facial PPE worn and the use of N95 respirators. 25 Another study in non-HCWs showed cloth masks led to fewer acne flares compared to surgical masks.…”
Section: Facial Ppementioning
confidence: 98%
“… 1 Rosacea Cheeks Doxycycline 40mg for 12 weeks Treatments provided clinical benefit Han C. et al 31 2020 China Non-HCWs 5 Acne Cheeks and nose Good response to Adapalene gel 0.1%, +/- face peel with 20% α-hydroxy acid Hu K. et al 22 2020 China HCWs 1 Acne Face Ferguson FJ. et al 16 2020 United Kingdom HCWs 16 Seborrheic Dermatitis Face 26 Acne 5 Rosacea Metin N. et al 24 2020 Turkey HCWs 82 Seborrheic Dermatitis Face and scalp 131 Acne/folliculitis Face Singh M. et al 17 2020 India HCWs 5 Acne Face Techasatian L., et al 25 2020 Thailand Both 333 Acne Face Trepanowski N. et al 32 2020 USA HCWs 11 Seborrheic Dermatitis Face 79 Acne 31 Rosacea Veraldi S. and Angileri L. 27 2020 Italy Both 20 Seborrheic Dermatitis Face …”
Section: Common Types Of Occupational Dermatitismentioning
confidence: 99%
See 2 more Smart Citations
“…Protective measures against COVID-19 include frequent hand washing and use of personal protective equipment (masks, gloves, shields, eye wear) leading to a high prevalence of occupational dermatoses among healthcare workers and in the general population. 23 Frequent handwashing has been reported to cause xerosis, irritant contact dermatitis, and even allergic contact dermatitis, as a result of frequent exposure to water, soaps, detergents that strip the skin of lipids, and use of hand sanitizers with high alcohol content. 24 Recommendations to alleviate xerosis and hand dermatitis include liberal application of moisturizers and ointments after handwashing and especially those that contain humectants such as urea, occlusive emollients, such as petrolatum, lanolin, and vegetable oils, or physiological lipids such as ceramides that replenish the depleted skin lipids and prevent dehydration.…”
Section: Ethnicity and Skin Barrier Functionmentioning
confidence: 99%